2021
DOI: 10.1002/eji.202048991
|View full text |Cite
|
Sign up to set email alerts
|

Geranylgeranyl pyrophosphate amplifies Treg differentiation via increased IL‐2 expression to ameliorate DSS‐induced colitis

Abstract: Blocking the mevalonate pathway for cholesterol reduction by using statin may have adverse effects including statin‐induced colitis. Moreover, one of the predisposing factors for colitis is an imbalanced CD4+ T cell, which can be observed on the complete deletion of HMG‐CoA reductase (HMGCR), a target of statins. In this study, we inquired geranylgeranyl pyrophosphate (GGPP) is responsible for maintaining the T‐cell homeostasis. Following dextran sulfate sodium (DSS)‐induced colitis, simvastatin increased the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…As a consequence, host cells down-regulate their lipid metabolism upon microbial sensing to protect the body from infection. Pathogens are sensed by TLR, that together with engagement of type I IFN receptors, have a general outcome to downregulate cholesterol metabolism in order to deplete energy reserves that might be used by the pathogen for propagation [41][42][43][44][45]. Coupled to this response is the regulation of the inflammatory cascade and the macrophage's effector function, demonstrating the intricate relationship between cholesterol metabolism and the immune response in innate immune cells.…”
Section: Cholesterol Immunometabolism In Innate Immune Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a consequence, host cells down-regulate their lipid metabolism upon microbial sensing to protect the body from infection. Pathogens are sensed by TLR, that together with engagement of type I IFN receptors, have a general outcome to downregulate cholesterol metabolism in order to deplete energy reserves that might be used by the pathogen for propagation [41][42][43][44][45]. Coupled to this response is the regulation of the inflammatory cascade and the macrophage's effector function, demonstrating the intricate relationship between cholesterol metabolism and the immune response in innate immune cells.…”
Section: Cholesterol Immunometabolism In Innate Immune Cellsmentioning
confidence: 99%
“…The provision of GGPP is also important, regulating autophagy, cell size and division in the Jurkat T cell line [114]. More recently, it has been shown that GGPP is a key metabolite in the maintenance of the Treg pool in a mouse model of colitis, amplifying Treg differentiation through STAT5 phosphorylation and decreasing pathogenic Th1 and Th17 responses [45]. The CBP also provides 7-dihydrocholesterol, the precursor of immunomodulatory vitamin D3, which has been directly implicated in the regulation of immune responses via its ability to induce the production of IL-10, a potent anti-inflammatory cytokine [115] and key to the immune-resolution process [116].…”
Section: T Cellsmentioning
confidence: 99%
“…Impairment of OXPHOS by deletion of its regulator proteins peroxisome proliferator-activated receptor γ coactivator 1α (Pgc1α) or sirtuin 3 (Sirt3), inhibits Treg functional fitness in vitro and in a mouse model of allograft survival [77]. Pandit et al [78] showed IL-2/STAT5 signaling is mediated through geranylgeranyl pyrophosphate. In a dextran sulfate sodium-induced colitis mouse model, they demonstrated that geranylgeranyl pyrophosphate-induced Ras/ERK enhanced IL-2 production in CD4 + T cells and lead to IL-2/STAT5 signaling to increase Treg differentiation and stability.…”
Section: Signaling Pathways Involved In the Treg Transition To Extregsmentioning
confidence: 99%
“…Pandit et al. [78] showed IL‐2/STAT5 signaling is mediated through geranylgeranyl pyrophosphate. In a dextran sulfate sodium‐induced colitis mouse model, they demonstrated that geranylgeranyl pyrophosphate‐induced Ras/ERK enhanced IL‐2 production in CD4 + T cells and lead to IL‐2/STAT5 signaling to increase Treg differentiation and stability.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a study using a T cell transfer colitis model demonstrated that CD4(+) T helper cells strongly contributed to the pathogenesis of IBD (Maschmeyer et al, 2021). In addition, imbalanced CD4+ T cells have been reported as predisposing factors for colitis (Pandit et al, 2021). Furthermore, mesalazine treatment mediated cytokine biosynthesis and secretion.…”
Section: Immunosuppressive Effect Of Mesalazine Via the Regulation Of Canonical Pathwaymentioning
confidence: 99%